Changes in Study Habits and Their Influence on Difficulties in Learning Accounting During the COVID-19 Pandemic - Imran, Ahmad Fadhil; Ikram, Alimul; Husni, Muhammad (FKIP-Universitas Riau, 2023)
The implementation of distance learning encourages all students to look for the best way so that learning effectiveness can be achieved while remaining aware of the spread of the coronavirus. The purpose of this study is to track the extent of study habits and their effect on learning difficulties in accounting during the COVID-19 pandemic. This study was conducted in order to determine the impact of the application of distance learning with the quantitative descriptive analysis method. Taking a population of all students of SMKN 4 Makassar with a sample of 76 people through the collection technique of proportionate stratified random sampling. Collecting data using instruments in the form of questionnaires and documentation. Data were analyzed by descriptive percentage and t-test. The findings of this study resulted in the equation model Y= 56.955-0.472X and the contribution of the independent variable to the dependent variable was 25,4%. That is, the study habits of students have a significant effect with negative results on learning difficulties in accounting. In other words, one of the factors that can overcome students’ accounting learning difficulties in the implementation of distance learning is by improving study habits.